Correlation between antenatal and postnatal coiling index and its role in prediction of perinatal outcome: A prospective cohort study - Ankita Kumari; Vani Aditya; Shaila Mitra; Garima Maurya; Pratima Sharma; Harish Chandra Tiwari (Asian Journal of Medical Sciences, 2025)
Background: The umbilical cord has pivotal role in the development, well-being, and survival of fetus and is vulnerable to kinking, torsion, and compression affecting perinatal outcome adversely. Aims and Objectives: This study was aimed to correlate the umbilical cord index measured antenatally using ultrasonography with that of the umbilical cord index measured postnatally and the association of this index with adverse fetal outcomes. Materials and Methods: This prospective cohort study was conducted on 124 antenatal cases of age group 18–35 years with term gestation with singleton pregnancy that attendant the outpatients department and indoor of Department of Obstetrics and Gynecology, Nehru Hospital B.R.D. Medical College, Gorakhpur over a period of 1 year (2019–2020). After detailed history, examination, and required antenatal care investigations, Ultrasonographic examination was done and antenatal umbilical coiling index (UCI) was calculated. The cases were followed up till delivery and postnatal UCI was also calculated and fetomaternal outcome was noted. Statistical analysis: Appropriate tests were applied where ever necessary. Results: The mean age was 25.71±4.30 years. The risk of preeclampsia, fetal growth restriction, oligohydramnios was significantly high with antenatal and postnatal hypocoiling (P<0.001) whereas the risk of gestational diabetes mellitus was significantly associated with antenatal and postnatal hypercoiling. The risk of low birth weight, preterm, low APGAR, neonatal intensive care unit admission and perinatal mortality were significantly high with postnatal hypocoiling (P<0.0001). Conclusion: The present study concludes that abnormal UCI was associated with adverse perinatal outcomes. Quantification of degree of abnormal coiling in antepartum period is important.